Rationale of ore transportation using cargo cableways at the Jeruy mine - Kushbakali Tazhibaevich Tazhibaev; Bubukan Kamardinovna Karabaeva; Daniyar Kushbakalievich Tazhibaev (REM: International Engineering Journal, 2025)
Abstract An analysis of existing flow technologies for use of cargo cableways to transport ore in mountainous deposits was carried out. Technical and economic calculations of the main indicators of ore transportation technologies for the use of a cargo cableway were carried out for the mountainous relief of the Jeruy gold deposit. A technical and economic comparison of technologies for transporting ore by truck and using a cargo cableway was carried out. The advantage of cargo cableways compared to automobile transportation is shown, especially in the conditions of difficult rugged mountainous terrain typical of the Jeruy deposit. As a result of enlarged calculations, the feasibility of using a cargo cableways in the conditions of the Jeruy gold deposit was substantiated for ore moving to the gold recovery plant (GRP), which will increase the economic indicators of the enterprise and improve the environmental situation at the mine due to a sharp harmful emission reduction from motor transport, and also increase the safety of mining operations at the mine.